Lipid droplet‐mediated lipid and protein homeostasis in budding yeast. Issue 8 (16th February 2018) - Graef, Martin
Abstract : Lipid droplets are conserved specialized organelles that store neutral lipids. Our view on this unique organelle has evolved from a simple fat deposit to a highly dynamic and functionally diverse hub—one that mediates the buffering of fatty acid stress and the adaptive reshaping of lipid metabolism to promote membrane and organelle homeostasis and the integrity of central proteostasis pathways, including autophagy, which ensure stress resistance and cell survival. This Review will summarize the recent developments in the budding yeast Saccharomyces cerevisiae, as this model organism has been instrumental in deciphering the fundamental mechanisms and principles of lipid droplet biology and interconnecting lipid droplets with many unanticipated cellular functions applicable to many other cell systems. Abstract :